Brand communication strategies of luxury hotels - Ten, Milena (2024)
The bachelor thesis explores the most effective brand communication methods used in the luxury hospitality sector. The thesis aims to identify persuasive strategies that luxury hotels use to engage consumers and enhance brand recognition. It covers key branding concepts like brand identity, image, and equity, while also examining consumer behavior, the role of technology, and the impact of digital platforms and social media. Through case studies of successful luxury hotels Four Seasons Paris, Armani Milano and Ritz Paris, the thesis highlights best practices in brand communication and concludes with recommendations of how luxury hotels can differentiate themselves in the market and foster a long-term loyalty.